Renewable energy in the global context - Maithani, P. C. (Concept Pub. Co., 2008)
Renewable energy covers a number of sources and technologies at different stages of development. Being environmentally benign and carbon free renewables are best suited to offset the challenges of global warming and climate change. In the three decades of concerted global developmental efforts it has started contributing significantly to the commercial energy mix. Many renewable energy technologies have matured over the last decade and moved from being a passion for the dedicated few to a major economic sector attracting large industrial companies and financial institutions. Renewable energy technologies such as wind power and solar photovoltaic devices have achieved major cost reductions over the last decade and are expected to continue to do so. This book provides an analysis of technology development trends at the global level future R & D directions for efficiency improvement and cost reduction and also the major challenges ahead. It also presents an overview of the policy regimes of major developed and developing countries. The externalities associated with energy and climate change linkages have also been examined. Apart from global renewable energy scene it has discussed the Indian renewable energy programme at length. Further it proposes a strategy for R & D and future policy directions for renewables in India.